Écran magique et prégnance du hors champ : l’art du cadrage dans « Mrs Bathurst » de Kipling - Élodie Raimbault (Cahiers Victoriens et Edouardiens)
The Bathurst « case » remains mysterious despite numerous explanatory attempts by critics, be they Charles Carrington or Philip Mason ; even an inquest such as Nora Crook’s fails to reveal the final truth about this story.« Mrs Bathurst » must certainly be seen rather as an experience on the narrative mode of the cinema. Philip French noted that it uses writing devices adapted from the cinema. It jointly presents two different modes of representation which rest on the question of point of view : a projection of live images and a subjective and mediatised narrative. The projection in the short story is in fact an apparition which turns people into ghosts or into fictional beings. Edgar Morin indeed noted that the early cinema transformed into a show what was not originally a show. In his short story, Kipling tackles the issue of the link between reality and magic as permitted by the cinema, and this maybe for the first time. The projection on a screen of images taken from reality paradoxically opens up onto the realm of fantasy and unreality.The frame, that is to say the delimitation of a point of view, is certainly what creates this magical effect and it is interesting to see that in « Mrs Bathurst » Kipling uses techniques which have a similar effect, such as elliptical statements, understatements, and unspoken comments. The obscurity of the story is not merely a loss, nor a gap, but also something which opens up the narrative possibilities. It reveals the presence of energetic unspoken elements. This is a short story which hinges on its off-screen and hidden dimension.